Pelatihan Digital Marketing bagi Pedagang Kecil di Gampong Keude Karieng untuk Meningkatkan Kepuasan Pelanggan - Aisyi, Rahadatul; Ummah, Rizky; Humaira, Rossa; Bila, Sasal; Al Ghifari, Aidil Fikri; Rambe, Ahmad Safri Noor; Akmal, Mulia; Asysyura, Asysyura; Zulkhairi, Zulkhairi (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2024)
This study aims to evaluate digital marketing training and mentoring for micro-entrepreneurs in Gampong Keude Karieng, Meurah Mulia District, North Aceh Regency. This activity was designed to increase the capacity of local entrepreneurs by utilizing digital technology in developing businesses. This research used a descriptive qualitative approach with a type of participatory action research. Data collection techniques were conducted using questionnaires, direct observation, in-depth interviews, and documentation. Data analysis techniques are carried out by analyzing qualitative data and quantitative data. The method used is a phased training approach, which starts with Problem Identification, Training Planning, Training Implementation which is divided into four sessions with digital marketing material involving 15 participants aged between 24 to 40 years, Evaluation and Follow-Up.  The results showed that the training successfully improved participants' understanding of the importance of digital marketing and its benefits for expanding market reach. However, there were challenges related to technological infrastructure, particularly unstable internet networks, as well as differences in motivation between young and more mature participants. The implications of this study suggest the importance of improving digital infrastructure in rural areas as well as the need for a more segmented approach based on age and experience to increase interest in entrepreneurship.